Development and validation in Ecuador of the EPD Questionnaire, a diabetes‐specific patient‐reported experience and outcome measure: A mixed‐methods study - Jimmy Martin‐Delgado; Aurora Mula; Mercedes Guilabert; Carlos Solís; Lorena Gómez; Gustavo Ramirez Amat; José Joaquin Mira; EPD Research Group (Wiley, 2022)
Abstract Introduction The global prevalence of diabetes in 2019 in adults was estimated to be 9.3%. This study developed in Ecuador, for the first time, instruments to assess patient‐reported outcomes and experiences. Methods The Experiences of the Person with Diabetes (EPD) Questionnaire is a diabetes‐specific instrument. A mixed‐methods study was conducted. First, a qualitative item development phase that included four focus groups and six semi‐structured interviews with patients was conducted in different rural and urban areas of Ecuador to obtain information on culture, beliefs, demographics, diet and social perspectives. A second quantitative phase for psychometric validation was carried out in primary care settings of rural and urban areas of Ecuador. Results Forty‐two and four hundred and eighty‐nine participants were included in each phase, respectively. The item development phase resulted in a questionnaire of 44 items (23 for perceived outcomes and 21 for experiences). In the validation study, most participants were women (58%) and from urban areas (57%). Exploratory factor analysis revealed three dimensions for each instrument. Outcomes instrument dimensions were symptoms and burnout, worries and fears and social limitations. Experiences instrument dimensions were information, patient‐centred care and care delivery. Cronbach's α values of the total score and dimensions were high, ranging between .81 and .93 in both instruments. Confirmatory factor analysis showed an acceptable fit of the data. Conclusion The EPD Questionnaire is probably the first instrument developed to assess patient‐reported experiences and perceived outcomes in a middle‐income country that included patients to capture all dimensions relevant for the intended population. Its psychometric properties are robust and could provide valuable information for clinicians and policymakers in the region. Patient or Public Contribution The development of these instruments has taken into consideration patients and the public since their conception. A qualitative approach gathered relevant information related to the cultural, social and economic burden of different populations in Ecuador. Before validation, a pilot test was carried out with users of the National Health Services to obtain their perspectives and insights of the developed instrument. Finally, during the data analysis, we have given special consideration to social variables such as rural and urban populations.